Human Rights and the Environment Philosophical, Theoretical and Legal Perspectives - Hajjar Leib, Linda (Queen Mary Studies in International Law, 2011)
The book examines the genesis and development of environmental rights (or the Right to Environment) in international law and discusses their philosophical, theoretical and legal underpinnings in the context of sustainable development and the notion of solidarity rights.